CYTOTOXIC ACTIVITY OF ERIOCAULON CINEREUM R.BR TO MCF-7 AND VERO CELL LINE - NUGRAHA, ARDE TOGA; PURNAMA, ASGAR; KOMARIAH, SITI NURUL; ANSHORI T., HADY (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of the study was to determine the strength of the Eriocaulon cinereum R.Br plant against breast cancer cells (MCF7) and cytotoxic against Vero cells. Methods: E. cinereum R.Br was taken from the province of Bangka Belitung and then extracted in stages with n-hexane, ethyl acetate, and methanol. Then, the ethyl acetate extract was fractionated using the vacuum liquid chromatography method with dichloromethane and ethyl acetate solvents. Sample was tested for MCF-7 cells and Vero cells using the MTT method (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide). The data obtained is analyzed by probit SPSS. Results: The results of this study showed that the best IC50 extract was ethyl acetate extract with an IC50 value of 450.31 μg/ml. Then, ethyl acetate extract produced dichloromethane fraction with IC50 value of 443.52 μg/ml and ethyl acetate with IC50 value of 214.75 μg/ml. Ethyl acetate fraction was also tested against Vero cells to see cytotoxic against normal human cells with IC50 679.11 μg/ml